Plan de negocios para la creación de un Restobar con temática japonesa - González Guerrero, Luis Eduardo (2025)
The business plan focuses on the creation of a Japanese-themed restobar in La Alborada, Guayaquil, which seeks to satisfy the growing demand for authentic and culturally enriching gastronomic experiences. This establishment will offer a unique value proposition by combining Japanese cuisine with cultural elements, allowing customers to immerse themselves in Japan's rich culinary tradition. The study approach is mixed, using quantitative and qualitative tools to collect relevant information. Interviews will be conducted with experts in the gastronomic and entrepreneurial sector to obtain perspectives on best practices and opportunities in the market. In addition, a survey will be carried out to collect statistical data on the preferences of the target audience and current demand in the market..........